HUBUNGAN MOTIVASI DAN PERHATIAN ORANG TUA TERHADAP HASIL BELAJAR SENI MUSIK DI SMP NEGERI 8 PAYAKUMBUH - Vovi Efriani; Jagar Lumban Toruan; Yuliasma Yuliasma (FBS Universitas Negeri Padang, 2013)
Abstarck This research is aim to get, to process, to analyze, and inrstigate data about correlation betwen study motivation and parent’s anttention to the study result of musical art in subjeck cultural art SMP N 8 Payakumbuh 2012/2013. Kind of research that use is correlational description. Population in this research is all student in grade VIII who study musical art in SMP N 8 Payakumbuh. There are 214 students. This research use 24 students. Instrumen that use is closed sample. Before doing the research, the first step is doing try out to considered validity and reliability the research instrumen. There are two analysis that use. They are (1) Descriptive analysis that aim to see mean, standar deviation, presentation, the number of group and interval. (2) Inferential analysis aim to test the hipothesis. The result show that (1) Variable of student motivation is good. (2) The correlation betwen study to study result is significant with contribution about 29% to variant variable of study result. (3) The correlation betwen parent’s attention to study result is significant with contribution about 18% to variant variable of study result. (4) The correlation betwen motivation and parent’s attention together are significant with contribution 29% to variant variable of study result. Keyword: Correlation ,Motivation, parent’s attention